Pelatihan dan Pendampingan Tata Kelola Website Perusahaan Outsourcing untuk Peningkatan Kapasitas Digital Operator Admin - Yanuangga Galahartlambang; Titik Khotiah; Ilham Basri K; Abdul Ghoffar (Journal of Community Service and Engagement, 2026)
This community service activity focuses on training and mentoring website management to improve the digital capacity of administrative operators at PT. Produktif Citrasukses, an outsourcing service company that manages the website www.diklatsatpam.com. This program is designed as a response to the gap between the quality of operational services and the limitations of human resource competencies in managing digital assets effectively. Initial assessments showed that the website was not being optimally utilized as a strategic communication medium due to inconsistent content management, a lack of governance standards, and the technical and managerial limitations of operators. The training program was implemented through hands-on practice covering the management of the main page, company profiles, news publications, gallery organization, and website theme customization. The evaluation results showed an increase in operator competence in content updates, more structured information presentation, and better visual consistency. This program also increased managerial awareness of the strategic role of websites in strengthening professionalism and public trust, as well as supporting the digital transformation of outsourcing service organizations.